A study of the use of free nicotine patches by Indigenous people - Rowena G. Ivers; Melissa Farrington; Chris B. Burns; Ross S. Bailie; Peter H. D'Abbs; Robyn L. Richmond; Eric Tipiloura (Elsevier, 2003)
Abstract Objective: To assess use of free nicotine patches by Indigenous people when offered a brief intervention for smoking cessation, and to assess changes in smoking behaviour at six months. Methods: We conducted a pre and post study in three Indigenous communities in the Northern Territory. Results: Forty Indigenous smokers self‐selected to receive free nicotine patches and a brief intervention for smoking cessation, and 71 chose the brief intervention only. Eighty‐four per cent of participants were followed up; 14% of participants could not be located. Fifteen per cent of the nicotine patches group (10% with CO validation) and 1% (CO validated) of the brief intervention only group reported that they had quit at six months. Seventy‐six per cent of the nicotine patches group and 51% of the brief intervention only group had reduced their consumption of tobacco. No participant completed a full course of patches. One possible side effect-the experience of bad dreams-was attributed in one community to the person concerned having been 'sung' or cursed. Conclusions: Free nicotine patches might benefit a small number of Indigenous smokers. Cessation rates for the use of both nicotine patches and brief intervention alone were lower than those in other populations, possibly because the study was conducted in a primary care setting and because of barriers to cessation such as widespread use of tobacco in these communities and the perception of tobacco use as non‐problematic.